2013
DOI: 10.1016/j.injury.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Sliding hip screw versus IM nail in reverse oblique trochanteric and subtrochanteric fractures. A study of 2716 patients in the Norwegian Hip Fracture Register

Abstract: 12 months postoperatively patients with transverse/reverse oblique trochanteric and subtrochanteric fractures operated with a SHS had a higher reoperation rate compared to those operated with an IM nail. Small differences regarding pain, satisfaction, quality of life, and mobility were also in favour of IM nailing. Consequently, a change in our treatment strategy for these fractures could be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 36 publications
1
88
0
3
Order By: Relevance
“…DHS, the most representative implant of extramedullary fixation, has been considered the gold standard for treatment of intertrochanteric fractures. However, the failure rate of DHS is higher [10,21] in the unstable and reverse oblique fracture, which limits its clinical use [11,16]. Gotfried developed the PCCP technique; however, the PCCP lengthens operation time and increases biomechanical complications [12].…”
Section: Introductionmentioning
confidence: 99%
“…DHS, the most representative implant of extramedullary fixation, has been considered the gold standard for treatment of intertrochanteric fractures. However, the failure rate of DHS is higher [10,21] in the unstable and reverse oblique fracture, which limits its clinical use [11,16]. Gotfried developed the PCCP technique; however, the PCCP lengthens operation time and increases biomechanical complications [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with unstable fracture patterns the results have been poor due to hardware related failure and lag screw cut-out [7]. Both biomechanical and clinical data suggest that CM nails have a mechanical advantage over extra-medullary implants in their ability to resist femoral shaft medialization and varus malunion, and this has led to the increased use of CM nails for hip fractures [8][9][10][11]. However, recent studies showed that there is still a high revision rate for unstable hip fractures treated with CM nails mainly due to cut-out of the lag screw [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, appropriate implants should be selected for fixation of the distal primary fragment, and postoperative stable reduction should be achieved. As clinical outcomes for the patients using SHS were poor, an intramedullary nail (IMN), such as SFN and long femoral nail (LFN), tended to be recommended [14][15][16][17][18][19]. However, it has not been clear whether LFN or SFN should be used in the different types of intertrochanteric fractures.…”
Section: Discussionmentioning
confidence: 99%